STUDI POLA PENATAGUNAAN POTENSI AIR SUMBER PITU DI WILAYAH KALI LAJING SEBAGAI DASAR PENGEMBANGAN SUMBER DAYA AIR WILAYAH SUNGAI AMPRONG - Haliem, Win; Juwono, Pitojo Tri; Priyantoro, Dwi (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2012)
The demand of water resource tends to increase due to the growth of population. Pitu Spring is a potential water source because it is a factor behind the idea of the utilization of non-irrigation to be used as the raw material of drink water.Result of optimization by considering the demand of irrigation water at Kedungkandang area indicates that the water stock is not enough if the Drink Water Company of Malang City is collecting standard water. The irrigation water system must be changed to SRI Method (System Rice of Intensification) because this system can save irrigation water by 48 %. The irrigation water scenario in the SRI system with the saving of irrigation water by 30% and 40 % can meet the demand of irrigation water, riparian water and standard water collection by Drink Water Company of Malang City until 2020 in constantly basis throughout year.region indicates that during rainy season, the demand of.Keywords: water resource, spring, optimization, riparian, and raw water